The terrestrial isopod fauna of Cheharmahal-va-Bakhtiyari Province - Ghasem Mohammadi Kashani; Ahdiyeh Abedini (علوم محیطی)
Introduction: Terrestrial isopods constitute the largest suborder in the order Isopoda and, as one of the main groups of soil decomposers, have an important role in acceleration of plant material recycling. Due to the shortage of studies on this taxon in southwestern Iran, the present study was carried out for the evaluation of terrestrial isopods biodiversity in Cheharmahal-va-Bakhtiyari Province. Material and methods: Sampling was performed throughout the province wherever potentially appropriate habitat for isopods existed. The collected specimens were preserved in 96% ethanol, and were then transported to the laboratory for further investigations. The isopods were dissected and micro-preparations of their diagnostic characters were slide-mounted in Euparal. Type material or original descriptions and illustrations of the species were used for species identification. Results and discussion: In the present work, totally 10 terrestrial isopod species were identified. Koweitoniscus tamei Omer-Cooper, 1923 from the family Eubelidae Budde-Lund, 1899 and Armadillidium vulgare Latreille, 1804 from the family Armadillidiidae Brandt, 1833 were reported. The species Agabiformius lentus Budde-Lund, 1885, Porcellionides pruinosus Brandt, 1833, Porcellio evansi Omer-Cooper, 1923 and P. mehrdadi Kashani et al., 2017 belonging to the family Porcellionidae Brandt & Ratzeburg, 1831 and Protracheoniscus major Dolfuss, 1903, P. ehsani Kashani, 2014, P. sarii Eshaghi, Kiabi & Kashani, 2015 and Mongoloniscus persicus Kashani, 2014 belonging to the family Agnaridae Schmidt, 2003 were identified. All species except Porcellio evansi and P. mehrdadi that were recently reported are new records for the province. Conclusion: the present study indicated that biodiversity of terrestrial isopods is relatively high in the province of Cheharmahal-va-Bakhtiyari, and further researches is essential for more precise estimation of the number of terrestrial isopod species in the province.